2003
DOI: 10.1046/j.1528-1157.2003.37802.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Analysis of the Interaction between Tiagabine and Midazolam with an Allosteric Model That Incorporates Signal Transduction

Abstract: Summary:Purpose: The objective of this study was to characterize quantitatively the pharmacodynamic interaction between midazolam (MDL), an allosteric modulator of the ␥-aminobutyric acid subtype A (GABA A ) receptor, and tiagabine (TGB), an inhibitor of synaptic GABA uptake.Methods: The in vivo concentration-response relation of TGB was determined through pharmacokinetic/pharmacodynamic (PK/PD) modeling. Rats received a single intravenous dose of 10 mg/kg TGB in the absence and the presence of a steady-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…An example of such a study is the work by Jonker et al [118] to assess the pharmacodynamic interaction between midazolam (an allosteric modulator for the GABA A -type receptor) and the anticonvulsant tiagabine (which inhibits the uptake of GABA at the synapse). The experiments demonstrated that midazolam and tiagabine express an additive in-vivo pharmacodynamic interaction, rather than synergistic.…”
Section: Prominent Drug Classes In the Realm Of Eeg Pharmacodynamimentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such a study is the work by Jonker et al [118] to assess the pharmacodynamic interaction between midazolam (an allosteric modulator for the GABA A -type receptor) and the anticonvulsant tiagabine (which inhibits the uptake of GABA at the synapse). The experiments demonstrated that midazolam and tiagabine express an additive in-vivo pharmacodynamic interaction, rather than synergistic.…”
Section: Prominent Drug Classes In the Realm Of Eeg Pharmacodynamimentioning
confidence: 99%
“…In order for this approach to succeed, such a model should be backed by substantial supportive evidence. For example, both the BZD drug class [112,113,114,115,116,117,118] and opioid drug class [104,105,106,107,108] have demonstrated a consistent EEG-concentration relationship that is well-characterized by pharmacodynamic models. The benefits of such a robust EEG-based pharmacodynamic model for drug development can include expediting clinical trials, enhanced clinical trial safety, reduction in clinical trial cost, or a combination of the three.…”
Section: Future Directions / Potential Applicationsmentioning
confidence: 99%
“…However, incorporating drug-target binding into the model might explain the same delay and could be more mechanistic [64]. On the other hand, when solving the shortcomings in knowledge on target site distribution of drugs, the principles of the operational model of agonism (receptor theory) will provide the basis for future developments in drug development by classifying drugs and predicting their mechanism of action in pharmacology [65][66][67][68]. PK-PD approaches have typically focused on anticipated drug effects.…”
Section: Cns Drug Effectsmentioning
confidence: 99%
“…Currently, to link (neuro-)PK to the systems response, PK-PD modeling is often applied. These models can include target activation (receptor theory [65][66][67][68]), signal transduction [57][58][59][60][61], interspecies differences [62], tolerance and sensitization [63], and intra-and interindividual variability. Also here, it should be noted that parameter values of PK, PD, and disease processes should not be obtained in isolation, and in different systems, because in such manner interrelationships and systems dependencies of processes cannot be assessed.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Inhibition of the enzyme GSK-3B, whose complete mechanism in relation with BD has not yet been hypothesized (Jonker et al 2003). 2.…”
Section: Biomarkers For Therapeutic Drug Monitoring In Psychiatry 31mentioning
confidence: 99%